2020
DOI: 10.1371/journal.pone.0243523
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral measures to fight COVID-19: An 8-country study of perceived usefulness, adherence and their predictors

Abstract: Behavioral measures, such as the wearing of facemasks and maintaining of distance to other people, have been central in fighting the COVID-19 pandemic and will continue to be important in curbing its spread. We therefore investigated their perceived usefulness, adherence and their predictors in representative online samples in eight countries (France, Germany, Poland, Russia, Spain, Sweden, U.K., U.S.). Of the 7,658 participants, 77.4% rated governmental measures (highest: Germany, lowest: France) as useful an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(157 citation statements)
references
References 47 publications
15
141
0
1
Order By: Relevance
“…Furthermore, stricter measures were imposed on older adults compared to the rest of the population, and measures were in general stricter in Ticino than in the rest of Switzerland. The ambivalence experienced by participants may be understood in light of an ambivalent attitude towards behavioral anti-COVID-19 measures showed by governments, as other studies have previously found [ 41 ]. Poor communication on the reasons behind such measures and on the differences between Ticino and Italy, and the rest of Switzerland, respectively, may have further contributed to increase participants’ uncertainty.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, stricter measures were imposed on older adults compared to the rest of the population, and measures were in general stricter in Ticino than in the rest of Switzerland. The ambivalence experienced by participants may be understood in light of an ambivalent attitude towards behavioral anti-COVID-19 measures showed by governments, as other studies have previously found [ 41 ]. Poor communication on the reasons behind such measures and on the differences between Ticino and Italy, and the rest of Switzerland, respectively, may have further contributed to increase participants’ uncertainty.…”
Section: Discussionmentioning
confidence: 84%
“…Literature on behavioural response to Covid-19 is fast emerging [13][14][15][16][17][18]. The limitations highlighted in the context of the pandemic literature prior to Covid-19 holds true for the more recent studies as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, few studies were created via international collaboration [52]. Additionally, cross-national research regarding mental health during the COVID-19 pandemic frequently refers to the general population [12,[29][30][31][53][54][55][56][57] rather than the student population [45,58,59]. Additionally, in articles related to students' mental health, a binational, rather than cross-national perspective appears more frequently [45,58,59].…”
Section: Introductionmentioning
confidence: 99%